Penguatan Kompetensi Guru Kompensatoris Melalui Lesson Study Berbasis Sekolah - Bastiana Bastiana; Risnawati Majit; Andhar Andhar; Futri Syam Wulandari; Lilis Nurindah Sari; Mirnawati Mirnawati (Universitas Negeri Makassar, 2022)
The purpose of this study is to determine the implementation of the lesson study program, especially in terms of: 1). Implementation of lesson study programs; 2). The role of lecturers, principals and special supervising teachers in the implementation of the lesson study program; 3). Impact of the implementation of the lesson study program. The findings of this analysis show that: 1). The lesson study program can be implemented because of the support of cooperation between lecturers, school principals and special supervisors in preparing the program. For special supervisor teachers, this program is very useful in providing services and education for students with special needs, as well as being able to gain competency abilities. Special supervising teachers are required to be able to plan lessons, practice these lessons, and receive input from facilitators (lecturers), school principals and other special supervising teachers; 2). There is support from the Ministry of Education and Culture, lecturers and school principals in the lesson study program. The principal's role includes support in implementation and mentoring. The role of lecturers includes providing training for lesson study programs. The role of the Ministry of Education and Culture in the lecturer and teacher partnership program includes support and funding of lesson studies; 3). The impact of the lesson study program for special mentor teachers is to improve the ability of teachers. They are more innovative with more varied learning methods and are more relevant to the ability level of students with special needs as well as increasing the quality and quantity of special tutors in providing special program services.